THE ACCOUNTANT'S PART IN DETERMINING STANDARDS. - Heckert, J. B. (The Accounting Review, 1933)
Abstract The article focuses on accountants' role in determining standards. It has come to a matter of general agreement that one of the primary purposes of accounting is to measure performance and promptly inform management when this performance is such as to merit special consideration. To measure either individual or group performance requires certain standards like collect and analyze statistical data which will be useful to those who must pass judgment on what constitutes good performance. Counsel with various executives upon whom these responsibilities fall. Record the standards set and their continuous revision. Inform those who set standards as to apparent discrepancies or errors. Promptly report variations between the actual performance and the standards, collecting and analyzing all data which tend to explain such variations. Translate the variations between actual and standard performance into such terms as will clearly and forcibly inform both executives and workers as to the ultimate results of such variations. Accumulate a story of individual or group performance in terms of the standards set.